2021
DOI: 10.1007/s11906-021-01156-3
|View full text |Cite
|
Sign up to set email alerts
|

Coffee and Arterial Hypertension

Abstract: Purpose of Review Coffee is a very popular drink and an estimated 2.25 billion cups worldwide are consumed daily. Such popularity of coffee makes it the most consumed drink next to water. Numerous studies have shown a beneficial effect of habitual and moderate coffee consumption on the functioning of the nervous, digestive, and cardiovascular systems, as well as on kidney function. Taking into account the very high prevalence of arterial hypertension in the world (31.1% of adults), much controv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 67 publications
1
38
0
5
Order By: Relevance
“…Similar results were reported in the studies by Zawadzki et al and Shaikh et al In these studies, coffee consumption was recognized as a risk factor for hypertension by nearly 64% and 35.5% of respondents, respectively [56,57]. In fact, a recent comprehensive review of the literature concluded that regular daily consumption of 2-3 cups of black coffee may reduce the risk of hypertension [36].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Similar results were reported in the studies by Zawadzki et al and Shaikh et al In these studies, coffee consumption was recognized as a risk factor for hypertension by nearly 64% and 35.5% of respondents, respectively [56,57]. In fact, a recent comprehensive review of the literature concluded that regular daily consumption of 2-3 cups of black coffee may reduce the risk of hypertension [36].…”
Section: Discussionsupporting
confidence: 77%
“…Our study also assessed factors that are not regarded as increasing hypertension risk, e.g., having home pets, consuming 2-3 cups of black coffee daily, vitamin D deficiency and female gender [19,36,61,62]. Although a large percentage of respondents had no knowledge of these factors, almost 1/5 of respondents stated that having home pets increases the risk of hypertension, and nearly 60% expressed the incorrect belief that coffee increases BP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the world, from a commercial point of view, the most important are Arabica coffee (Coffea arabica), Robusta coffee (Coffea canephora) and Liberian coffee (Coffea liberica) [3]. The largest amounts of coffee are produced in Brazil [1].…”
Section: Coffee -An Overview Of the Most Important Informationmentioning
confidence: 99%
“…Consuming coffee, especially brewed with a paper filter and without the addition of sugar or milk, in a regular and moderate manner (2-3 cups/day) has a beneficial effect on human health in the general population. It was shown that consumption of coffee according to such a pattern was characterized by antihypertensive properties and had a positive effect on the activity of the nervous, digestive, cardiovascular and kidney systems [3,[8][9][10][11]. In a recent study by Simon et al [12], including 468,629 subjects, drinking 0.5-3 cups of coffee/day was associated with a lower risk of death from any cause [HR (hazard ratio) = 0.88; 95% CI (confidence interval): 0,83-0.92; p < 0.001] and death from cardiovascular causes (HR = 0.83; 95% CI: 0.74-0.94; p = 0.006), and stroke (HR = 0.79; 95% CI: 0.63-0.99 p = 0.037) during 11 years of follow-up.…”
Section: Coffee -An Overview Of the Most Important Informationmentioning
confidence: 99%